Una Vida Sin Palabras - Isenberg, Adam (Turkey, 2011)
Born deaf on a farm in Nicaragua, Dulce Maria (28) and her brother Francisco (22) have never been free to stray more than a few miles from their rural home. The result: they know no language at all--written, spoken or signed. If victimized, they have no way to report it. They don't know their own names, or even that such a thing as names exist. They are entirely locked out of fundamental knowledge, having never had a conversation with anyone. This begins to change when they are visited by a deaf sign-language teacher, working for a local NGO, who comes to their village determined to teach them their first words. The film is an intimate portrait of a very special family and brings to light a human rights issue few have ever considered.
Verzio Film Festival Submission
Verzio Film Festival Submission
Keywords: Documentary films